Kegiatan Charity Himasi Untuk Membentuk Rasa Kepedulian Mahasiswa Dengan Cara Berbagi Takjil Di Panti Asuhan Daarus Sholihin Kota Cirebon - Raden Muhamad Rama Poetra Ardiningrat; Dwi Pasha Anggara Putra; Marsani Asfi (CV. Akira Java Bulu, 2025)
University students play a vital role as agents of change, not only by achieving academic excellence but also by contributing meaningfully to society. One such contribution is through charity activities that foster empathy and social awareness. The 2025 charity event organized by the Information Systems Student Association (HIMASI) of UCIC aimed to cultivate students’ social concern through direct interaction with children at the Daarus Sholihin Orphanage in Cirebon. The implementation method consisted of three stages: planning, execution, and evaluation. The main activities included the distribution of takjil (light meals for breaking the fast), social interaction sessions, and evaluation through group discussions. The results showed that students experienced increased empathy, teamwork skills, and social awareness. Meanwhile, the children responded positively to the attention and engagement provided. This activity not only benefited the recipients but also served as a medium for character development among students. In conclusion, this charity activity effectively fosters social concern and can be developed into a sustainable program through various other forms of social engagement.